Rhetoric and scripture: collected essays of Thomas H. Olbricht - Olbricht, Thomas H. (Emory studies in early christianity, 2021)
"This book offers a unique overview of the development of rhetorical criticism both in North America and internationally through the work of pioneering New Testament scholar Thomas H. Olbricht. Nineteen essays cover four areas related to rhetorical criticism: the history of biblical rhetorical analysis, the rhetorical analysis of biblical texts, the characteristics of rhetorical analysis, and types of biblical rhetorical criticism. A foreword by Lauri Thurén and a memorial essay by Carl R. Holladay contextualize Olbricht's work. Anyone interested in the rhetorical study of the New Testament will find this volume inspiring and informative"--Publisher